1969
DOI: 10.1172/jci106170
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the pituitary-Leydig cell axis in young men with hypogonadotropic hypogonadism and hyposmia: comparison with normal men, prepuberal boys, and hypopituitary patients

Abstract: A B S T R A C T Pituitary and gonadal function was studied in seven chromatin-negative men, ages 15-27 yr, with retarded sexual and somatic development, skeletal anomalies, and hyposnmia. These hyposmic patients were compared with normal men, prepuberal boys and hypogonadal patients with hypopituitarism. The urinary follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels of hyposmic subjects were the same as those of normal boys and hypopituitary patients but significantly lower than those of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0
1

Year Published

1971
1971
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(43 citation statements)
references
References 32 publications
7
35
0
1
Order By: Relevance
“…A previous study separated gonadotropinrepresented isolated, sporadic occurrences. In addition deficient from normal adult males by measuring immunoto the findings of hypogonadism in all subjects, only reactive FSH and LH in urine extracts (17). In the L. E. displayed other anomalies, specifically anosmia and present study, radioimmunoassay of a single blood sample unilateral renal agenesis, an association previously re-for both FSH and LH permitted us to clearly separate viewed by Nowakowski and Lenz (7).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…A previous study separated gonadotropinrepresented isolated, sporadic occurrences. In addition deficient from normal adult males by measuring immunoto the findings of hypogonadism in all subjects, only reactive FSH and LH in urine extracts (17). In the L. E. displayed other anomalies, specifically anosmia and present study, radioimmunoassay of a single blood sample unilateral renal agenesis, an association previously re-for both FSH and LH permitted us to clearly separate viewed by Nowakowski and Lenz (7).…”
Section: Resultssupporting
confidence: 56%
“…Plasma testosterone was in the normal adult male range in all subjects during HCG administration. 6 ness in affected individuals becomes paramount since separate normal from low levels (17,(27)(28)(29)(30). This may the success of newer modes of therapy in this disorder be related to methodology, since both precision and sensiwill depend on such responsiveness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision of the assay was determined by assaying 20 (20). Plasma U-1 and FSH were measured during clomiphene citrate administration (200 mg/day for 6 days) (15,21). ACTH reserve was tested by the administration of Metopirone, 2.0 or 3.0 g in a single dose followed by the measurement of 11-deoxycortisol in serum 8 h later (16).…”
Section: Hormone Assaysmentioning
confidence: 99%
“…Received for publication 21 (FSH) were secreted continuously in man with resultant constant serum levels. However, several investigators have recently demonstrated that LH is secreted in a pulsatile fashion in man as well as in other species (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%